Development and optimization of plasmonic nanostructures for surface-enhanced Raman scattering - Quan, Lam Zhung (2015)
Surface-enhanced Raman scattering (SERS) exploits the gigantic enhancement of inherently weak Raman signal by intensive interaction of light with molecular species adsorbed on the surface of carefully designed substrate having nanometric roughness. Today, trinitrotoluene (TNT) and melamine contamination are of major concern due to their toxicity and health hazards on human. Therefore, it is important to develop a sensitive and cost-effective probe for the detection of these contaminants in trace amount. First, I designed a cysteine-modified 40 nm gold nanoparticles (AuNP) substrate for selective and sensitive detection of TNT. Due to the formation of Meisenheimer complex upon TNT addition, aggregation between Meisenheimer complex bound AuNP and cysteine-modified AuNP was observed. This study demonstrated that TNT can be detected in 1 nM level with excellent discrimination against other nitro compounds. Second, I introduced a novel silver-coated gold nanostars (Au@AgNS) substrate via seeded-growth method. Au@AgNS with gold to silver ratio of 1:0.25 was demonstrated to achieve the highest intensity through optimization study. By taking advantage of the presence of sharp features and superior optical properties of silver, a detection limit of 1 µM level of melamine can be obtained.